Implementasi Program Pembiasaan Kompetensi Spiritual dalam Membentuk Nilai-Nilai Karakter Siswa di SD Negeri Menjer - Laila Maida Karima; Ahmad Khoiri; Vava Imam Agus Faisal (AL KAYYIS, 2026)
This study aims to describe the implementation of the Spiritual Competence Habituation Program in shaping students’ character values at SD Negeri Menjer, its contribution to character development, and the supporting and inhibiting factors in its implementation. This research employed a qualitative approach using a field study method. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The findings show that the program is systematically implemented through the stages of planning, implementation, and evaluation with main activities such as congregational Dhuha and Dhuhr prayers, Asmaul Husna recitation, and Qur’an memorization (muraja’ah). The program contributes significantly to the development of students’ religious character, discipline, and responsibility through continuous and structured habituation. Supporting factors include the principal’s commitment, teachers’ role modeling, students’ active participation, and a religious school culture, while inhibiting factors include limited facilities, weather conditions, and differences in students’ abilities. The study concludes that spiritual habituation is effective in strengthening character education when supported by collaboration among school members and consistent implementation of activities.